Kikuchi’s Disease: A Case Report (Bangladesh Journal of Otorhinolaryngology, 2020)
A 30-year-old female attended in August 2019, presented with painful swelling in right upper neck and fever for 20 days. Biochemical and microbiological tests, and imaging studies were all inconclusive. Histopathology of the affected lymph nodes revealed consistent with Kikuchi’s disease. The Patient was treated properly and complete remission occurred within few weeks. It is a self-limiting idiopathic disease which can mimic several serious conditions such as TB, lymphoma, infectious mononucleosis and others.Bangladesh J Otorhinolaryngol; October 2019; 25(2): 125-127